Réponses

Meilleure réponse !
2012-10-30T10:48:16+01:00

ex2 :

 

c)(2x+5)(3x+7)

2x*3x+2x*7+5*3x+5*7

6x²+14x+15x+35

6x²+29x+35

 

d)(5x+8)(2x-7)

5x*2x+5x*(-7)+8*2x+8*(-7)

10x²-35x+16x-56

10x²-19x-56

 

e)(2x-5)(3x-2)

2x*3x+2x*(-2)-5*3x-5*(-2)

6x²-4x-15x+10

6x²-19x+10

 

f)(2+x)(5x-4)

2*5x+2*(-4)+x*5x+x*(-4)

10x-8+5x²-4x

5x²+6x-8

 

ex72 :

 

a)(2x+3)(4x+1)

2x*4x+2x*1+5*4x+3*1

8x²+2x+12x+3

8x²+14x+3

 

b)(3x-1)(2x+4)

3x*2x+3x*4-1*2x-1*4

6x²+14x-2x-4

6x²+12x-4

 

c)(5x+1)(2x-4)

5x*2x+5x*(-4)+1*2x+1*(-4)

10x²-20x+2x-4

10x²-18x-4

 

d)(2x-5)(4x-3)

2x*4x+2x*(-3)-5*4x-5*(-3)

8x²-6x-20x+15

8x²-26x+15

2012-10-30T11:32:43+01:00

exercice n°2

C=(2x+5)(3x+7)

C=2x*3x+2x*7+5*3x+5*7

C=6xcarré+14x+15x+35 =6xcarré+29x+35

 

D=(5x-8)(2x-7)

5x*2x-5x*7-8*2x-(-8*7)=10x carré-35x-16x+56=10xcarré-51x+56

 

E=(2x-5)(3x-2)

2x*3x-2x*2-5*3x-(5*-2)=6xcarré-4x-15x+10=6xcarré-19x+10

 

F=(2x+5)(5x-4)

2x*5x-2x*4+5*5x-5*4=10xcarré-8x+25x-20=10xcarré+17x-20

 

n°72

A=(2x+3)(4x+1)

8xcarré+2x+12x+3=8xcarré+14x+3

B=(3x-1)(2x+4)

6xcarré+12x-2x-4=6xcarré+10x-4

C=(5x+1)(2x-4)

10xcarré-20x+2x-4=10xcarré-20x-4

D=(2x-5)(4x-3)

8xcarré-6x-20x+15=8xcarré-26x+150bonne chjance